2020
DOI: 10.1108/ijpsm-06-2019-0177
|View full text |Cite
|
Sign up to set email alerts
|

Performance reporting delay in local government: a global south view

Abstract: PurposeThe object of this paper is to understand how central–local relations and internal technical characteristics contribute to performance reporting delays at the local level in a Global South context.Design/methodology/approachThe paper develops and tests four propositions using a combination of secondary data analyses and semistructured interviews with 30 local government officials.FindingsThe findings indicate that delays in performance reporting are generally high in pre-election years because leadershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Previously, Vignieri (2018) had reported that failure to conduct performance audit to establish irregularities rendered regulation on performance measurement powerless. A recent study, on another hand, by Kaye-Essien (2020), reported that lack of noncompliance sanctions contributed to delayed performance reporting in subnational governments. As such, this study amplifies the argument by the institutional theory on the role of coercive pressure through legal framework to promote adoptions of formal structures within organizations.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Previously, Vignieri (2018) had reported that failure to conduct performance audit to establish irregularities rendered regulation on performance measurement powerless. A recent study, on another hand, by Kaye-Essien (2020), reported that lack of noncompliance sanctions contributed to delayed performance reporting in subnational governments. As such, this study amplifies the argument by the institutional theory on the role of coercive pressure through legal framework to promote adoptions of formal structures within organizations.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The reasons for the central government to control the regions, especially those related to regional expenditure management, are generally analyzed based on three arguments, namely about tax delegation, the imperfection of local democracy combined with the effects of distribution, and the third consideration of the egoism of local politicians (Fender & Watt, 2002). In addition, the central government's control of this region is also related to performance management (Arribas, 2016;Kaye-Essien, 2020).…”
Section: Planning Becomes Part Of the Local Governance Cyclementioning
confidence: 99%